Association of vitamin D with HIV infected individuals, TB infected individuals, and HIV-TB co-infected individuals: a systematic review and meta-analysis - Xie, Kaidi; Zhang, Yang; Zhang, Mei; Wu, Hao; Zheng, Luyao; Ji, Jiahao; Li, Zhen; Wang, Wen; Zhang, Tong (Frontiers in Public Health, 2024)
Background Vitamin D deficiency (VDD) is a worldwide disease. VDD is also associated with an increased risk of HIV-related comorbidities and mortality, and patients have a tendency to develop active tuberculosis compared to those with latent tuberculosis infection. Vitamin D supplementation may modulate HIV replication, improve TB inflammation and reduce progression of HIV-TB co-infection. Methods We meta-analyzed individual participant data from cohort studies, cross-sectional study, and RCTs of vitamin D in HIV group, TB group, and HIV-TB group. The primary outcomes were differences in vitamin D level and VDD prevalence between three groups, the secondary outcomes were CD4 count, HIV viral load, time to sputum smear conversion, time to culture conversion, relapse, morality, and TB score. Results For vitamin D levels, the overall mean difference (MD) between HIV group and TB group was −0.21 (95% CI, −20.80–20.38; p = 0.9, I2 = 84%), HIV group and HIV-TB group was 0.87 (95% CI, −11.45–13.20; p = 0.89, I2 = 87%), and TB group and HIV-TB group was 1.17 (95% CI, −5.21–7.55; p = 0.72, I2 = 85%). For vitamin D deficiency prevalence, the overall odds ratio (OR) for HIV group versus TB group was 1.23 (95% CI, 0.46–3.31; p = 0.68; I2 = 70%), HIV group versus HIV-TB group was 1.53 (95% CI, 1.03–2.29; p = 0.04; I2 = 0%), and TB group versus HIV-TB group was 0.85 (95% CI, 0.61–1.20; p = 0.36; I2 = 22%). In HIV-TB group, the overall OR for vitamin D group versus placebo group was 0.78 (95% CI, 0.34–1.67; p = 0.52; I2 = 60%). Conclusion Our findings indicated that there were no variations in vitamin D levels between three groups. The prevalence of vitamin D deficiency was higher in the HIV-TB group than in the HIV group. Additionally, the administration of vitamin D supplements did not have obvious impact on CD4 count and viral load. Likewise, vitamin D had no effect on time to sputum smear conversion, time to culture conversion, relapse, 12-month morality, and TB score.